THE INFLUENCE OF SOCIAL NETWORKS ON THE PSYCHOLOGY AND BEHAVIOR OF ADOLESCENTS (Universal International Scientific Journal, 2026)
This article discusses the impact of social networks on the psyche and behavior of adolescents. It is no exaggeration to say that social networks, which attract adolescents, have become a pressing problem of today. Human psyche and behavior are delicate issues. This is known to everyone. Adolescence is a period of significant physiological and neurohumoral changes in the human body. These changes, in turn, cause a number of negative consequences.
Keywords: psychology; social media; stress